Usability Testing Pada Situs Web UKK PUSBANGKI Menggunakan Metode Cognitive Walkthrough - Hidayah, Nur Aeni; Abdul Malik, Dani (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
UKK PUSBANGKI takes advantage of advances in information technology, namely by using the website (pusbangki.id) as a means to encourage the creation of visionary business cooperation programs. UKK PUSBANGKI has never conducted usability testing on the pusbangki.id website, so there is a need for usability testing to help evaluate the pusbangki.id website so as to assist in developing the website as one of the websites that has a major impact for UKK PUSBANGKI. The method used in this study is Cognitive Walkthrough, which aims to provide a tool to assess the usability of a system, and determine the causes of usability problems on websites. The results of the analysis show that task scenario 1 achieves a success rate of 90%, task scenario 2 achieves a success rate of 70%, task scenario 3 achieves a success rate of 100%, and task scenario 4 achieves a success rate of 60%.